2016
DOI: 10.1111/all.12909
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation during pregnancy and infancy reduces aeroallergen sensitization: a randomized controlled trial

Abstract: Vitamin D supplementation during pregnancy and infancy reduces the proportion of children sensitized to mites at age 18 months. Preliminary data indicate a possible effect on primary care visits where asthma is diagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 42 publications
2
61
1
2
Order By: Relevance
“…Higher IgE levels have been shown to correspond with low vitamin D status in allergic individuals (5). A recent study showed that vitamin D supplementation of pregnant women resulted in lower serum IgE levels to mite antigens in the babies born to the vitamin D supplemented women (6). Vitamin D is a potential regulator of serum IgE and therefore susceptibility to allergic asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Higher IgE levels have been shown to correspond with low vitamin D status in allergic individuals (5). A recent study showed that vitamin D supplementation of pregnant women resulted in lower serum IgE levels to mite antigens in the babies born to the vitamin D supplemented women (6). Vitamin D is a potential regulator of serum IgE and therefore susceptibility to allergic asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Grant et al [101] randomized 260 woman/infant pairs to placebo/placebo, 1,000 IU/400 IU or 2,000 IU/800 IU. At enrolment, the mean serum 25(OH)D value was above the deficient level (63 nmol/L or 25 ng/mL).…”
Section: Prenatal Vitamin D Status and Asthma Riskmentioning
confidence: 99%
“…The results obtained from a double-blind, randomized, parallel-group, placebo-controlled trial have revealed that supplementation of women (1000 IU/2000 IU) and infants (400 IU/800 IU) decreased sensitization of children to mites at 18 months [37].…”
Section: Pregnant Womenmentioning
confidence: 99%